PENGARUH SUSU SKIM TERHADAP PENAMPILAN AYAM PETELUR JANTAN - Sulis Dianto; Agustina Widyasworo Kunharjati (Universitas Islam Balitar, 2017)
One effort to improve the efficiency and effectiveness of the production of roaster of broiler, can be done by improving the quality of feed is one of the skim milk dairy products in the solid form with the potential to supply poultry feed. Skim milk contains all the nutrients of milk except fat and vitamins that are fat soluble. This study aims to determine the effect of skim milk on the growth of roaster of broiler. Research using experimental design completely randomized design (completely randomized design). The material used in this study were male laying hens as much as 60 head aged 30 days to harvest at the age of 58 days. Skim milk from KUD Cement. Feed used is BR 1 of PT. Cargill Indonesia. Stage enclosure for maintenance, measuring 2m x 1.5m and is divided into 12 plots and each 1 plot size is 50cm x 50cm, each plot contained 5 chickens. The variables in this study were feed consumption, body weight gain and feed conversion ratio (FCR). Research results obtained three conclusions that the addition of skim milk significant effect (P> 0.01) on increasing body weight roaster of broiler P1 = 120 g / head / week. The addition of milk skin significant (P> 0.01) in penurunkan figures feed convertion ratio (FCR) roaster of broiler by P1 = 1.90. Treatment addition of 7.5% skim milk gives the best effect on improving body weight gain and feed convertion ratio (FCR) of roaster of broiler. Based on the results of the study suggested, adding skim milk can be used up to the level of 7.5% in the diet of roaster of broiler, but need considering economic efficiency.Keywords: Skim milk, appearance, roaster of broiler.